An interval type-2 fuzzy AHP approach for success factors of green supply chain management - Davod Andalib Ardakani; Mehrdad Kiani; Ali Saffari Darberazi; Fatemeh Zamzam; Elham Mofatehzadeh (International Journal of Research in Industrial Engineering)
This study aimed to design a model for identifying and ranking the factors influencing green supply chain management in the tile and ceramic industry, a significant industry in Iran. The study consisted of three main stages. In the first stage, a systematic review of the literature and the Meta-synthesis method were employed to identify and categorize the factors that contribute to the success of green supply chain management. The factors were thoroughly examined and refined in the second stage using the content validity method. As a result of these steps, a comprehensive model was developed, comprising 30 factors categorized into six dimensions: green suppliers, green technology and expertise, green human resources, green products, green organization and communications, and green regulations and support. In the third stage, the Interval Type-2 Fuzzy Analytic Hierarchy Process (IT2FS-AHP) method was utilized to rank the dimensions and factors. Experts' opinions were gathered through a questionnaire to determine the importance of each dimension and factor. The results indicated that the dimensions of green technology, expertise, and green regulations and support were deemed the most critical. Furthermore, factors such as "attention to social responsibility in the organization," "design and development of evaluation and selection systems of suppliers based on environmental criteria," and "support of operational, middle, and senior managers in implementing the green supply chain" were identified as highly influential in the success of green supply chain management. Overall, identifying and ranking key factors in green supply chain management contributes to mitigating the adverse environmental impact of industrial activities and enhancing customer satisfaction.